Polityka Stanów Zjednoczonych Ameryki wobec Bliskiego Wschodu w trakcie prezydentury Baracka Obamy - Habowski, Mirosław (Instytut Studiów Międzynarodowych Uniwersytetu Wrocławskiego, 2015)
In relation to the period when G.W. Bush stayed in office, under B. Obama’s presidency the nature of the USA’s policy towards the Middle East has been changed as far the used tactics is concerned. The United States avoided direct employment of troops in the region on a large scale. They started to prefer proxy war tactics, support the Sunnis against the Shias and Christians. They have also decreased verbal (but not real) support for Israel. The US forced Iran to join negotiations on the nuclear programme carried out by this state and entered into an appropriate agreement while implementing actions aimed at overthrowing the pro-Iranian government in Damascus by supporting the Islamic (Sunni) opposition. It seems that the strategic goal of the American policy, i.e. maintaining the US global hegemony, has been upheld
Keywords: Barack Obama; polityka zagraniczna USA; Bliski Wschód; wojna domowa w Syrii; realizm; irański program atomowy; promocja demokracji; uniwersalne prawa; imperium